Phase shift of polarized light through sculptured thin films：Experimental measurements and theoretical study - 侯永强 齐红基 李煦 何凯 易葵 邵建达 (Chinese physics B, 2013)
A slanted columnar TiO2 sculptured anisotropic thin film （ATF） is prepared via the glancing angle deposition technique and used as the phase retardation plate. The tilted nanocolumn microstructures of thin film induce the optical anisotropy. With the biaxial birefringent model, the optical constants dispersion equations of TiO2 ATF are derived by fitting the transmittance spectra for s-and p-polarized waves measured at normal and oblique incidence within 400 nm–1200 nm. The phase shift of polarized light after reflection and/or transmission through the TiO2 ATF is analyzed with the characteristic matrix employing the extracted structure parameters. The theoretical studies reasonably well accord with the experimental results measured with spectroscopic ellipsometry. In addition, the dependences of the phase shift on the coating physical thickness and oblique incidence angle are also discussed. Birefringence of the biaxial ATF provides a sophisticated phase modulation by varying incidence angles over a broad range to have a wide-angle phase shift.